Answer:
x = 1, -2/7
Step-by-step explanation:
You could use the quadratic equation but this can be factored into
(7x + 2) (x - 1). You can verify that by multiplying it out.
Since (7x + 2) (x - 1) = 0, if either factor is 0 then the equation would be equal to 0, thus we get x = 1, -2/7
Length times width times height gives you the volume of things
Answer: 14x^2 - 84x - 7
====================================================
Explanation:
The like terms 6x^2 and 8x^2 combine to 14x^2
The like terms -8x and -76x combine to -84x
Nothing pairs with the -7, so its stays as is.
Standard form is where we list the terms in decreasing exponent order. We can think of -84x as -84x^1 and the -7 as -7x^0. So 14x^2 - 84x - 7 would be the same as 14x^2 - 84x^1 - 7x^0. The exponents count down: 2,1,0.
The final answer is a trinomial since it has three terms. It is also a quadratic because the degree (highest exponent) is 2.
Answer:
please mark my answer brainliest
Step-by-step explanation:
- 11 students
- 26 students
- that 2 small divisions =1 unit =1 student